Soaked Water of Rice Straw Ash and Ziziphus mauritiana Leaf Extract as Disinfectant: A Microbiological Assessment - Yulia, Yulia; Amaliyah, Nurul (Ahmar Metastasis Health Journal, 2025)
Commercial dishwashing liquids contain chemicals that are extremely toxic to humans and the environment, hence alternative dishwashing using natural compounds is urgent. The purpose of this study was to evaluate the effect of a combination formula of rice straw ash and Ziziphus mauritiana leaf extract (JEBI) in reducing germs colonies per food equipment. This experimental study has a pre-post-test design with a control group. The variations of the JEBI combination used are 1:1, 1:2, 1:3, 2:1, and 3:1. Another treatment is using a commercial dishwasher brand "X" and only running water. A total of 210 cutleries (plates and bowls) from 30 restaurants in six districts were taken randomly—calculation of bacterial colonies using the Total Plate Count Agar method. The results were analyzed using one-way ANOVA to compare the effect between treatment groups on germ counts. Overall, a significant difference between the JEBI combination and the number of germs on food equipment was present in this study (p<0.001). The 1:3 JEBI ratio reduced the highest number of germs (average 24.6 colonies/cm2), slightly better than using "X" dishwashing liquid (average 25.6 colonies/cm2). Additionally, all treatments gave a significant reduction of germs compared to washed cutleries without any disinfectant (p<0.001). These findings strengthen the potential disinfectant function of rice straw ash and Ziziphus mauritiana leaf extract (JEBI) against germs on cutleries. Further studies with different ratio formulas and better study designs are required to obtain better and more precise results.